2022
DOI: 10.1101/2022.03.31.486637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different olfactory neuron classes use distinct temporal and molecular programs to complete synaptic development

Abstract: Developing neurons must meet core molecular, cellular, and temporal requirements to ensure the correct formation of synapses, resulting in functional circuits. However, because of the vast diversity in neuronal class and function, it is unclear whether or not all neurons use the same organizational mechanisms to form synaptic connections and achieve functional and morphological maturation. Moreover, it remains unknown if neurons united in a common goal and comprising the same sensory circuit develop on similar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
(197 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, a recent study demonstrated that during the time window of homeostatic compensation, i.e. the first day post-eclosion, ORNs and PNs show structural changes involving increased Brp expression and neurite expansion, while iLNs do not 69 . It is conceivable that this developmental stability prevents or limits structural homeostatic plasticity at ORN-iLN synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that during the time window of homeostatic compensation, i.e. the first day post-eclosion, ORNs and PNs show structural changes involving increased Brp expression and neurite expansion, while iLNs do not 69 . It is conceivable that this developmental stability prevents or limits structural homeostatic plasticity at ORN-iLN synapses.…”
Section: Discussionmentioning
confidence: 99%